2020
DOI: 10.1039/c9pp00311h
|View full text |Cite
|
Sign up to set email alerts
|

Hematoporphyrin monomethyl ether-mediated photodynamic therapy inhibits the growth of keloid graft by promoting fibroblast apoptosis and reducing vessel formation

Abstract: Photodynamic therapy (PDT) has been shown to significantly inhibit fibroblast activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The PDT, together with the photosensitizer 5-ALA, has previously been reported to induce apoptosis in fibroblasts and reduce the growth of a keloid graft. 23 It has also been observed previously that HMME-PDT treatment enhances the apoptosis rate of keloid fibroblasts. 23 In the current study, PDT and the photosensitizing agent Ph1 were investigated under different conditions and light powers both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The PDT, together with the photosensitizer 5-ALA, has previously been reported to induce apoptosis in fibroblasts and reduce the growth of a keloid graft. 23 It has also been observed previously that HMME-PDT treatment enhances the apoptosis rate of keloid fibroblasts. 23 In the current study, PDT and the photosensitizing agent Ph1 were investigated under different conditions and light powers both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 59%
“…23 It has also been observed previously that HMME-PDT treatment enhances the apoptosis rate of keloid fibroblasts. 23 In the current study, PDT and the photosensitizing agent Ph1 were investigated under different conditions and light powers both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Cai et al ( 30 ) further demonstrated that HMME-PDT could induce apoptosis of scar fibroblasts and stimulate production of caspase-3, a key enzyme in cell apoptosis. Consistently, the group of Cui ( 31 ) showed that HMME-PDT promotes fibroblast apoptosis and reduces vascular density and scarring in nude mice. The cumulative effect of two consecutive HMME-PDT sessions, which achieved good results in patients with PDL treatment history, should also be considered.…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, in terms of treatment history, favorable efficacy was achieved for all three categories of patients, suggesting no effect of PDL treatment history on efficacy of the dual HMME-PDT treatment regime. One hypothesis to explain this finding is that with repeated application, HMME-PDT improves perivascular Consistently, the group of Cui (31) showed that HMME-PDT promotes fibroblast apoptosis and reduces vascular density and scarring in nude mice. The cumulative effect of two consecutive HMME-PDT sessions, which achieved good results in patients with PDL treatment history, should also be considered.…”
Section: Discussionmentioning
confidence: 86%